1982
DOI: 10.1007/bf01451652
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on a detergent system with rodlike micelles

Abstract: Conductivity, kinetic, static and dynamic light scattering, electric birefringence and rheological measurements were carried out on aqueous solutions of Tetradecylpyridinium-n-Heptanesulfonate (C14PyCTSO3) up to high concentrations. In dilute solutions between the critical micelle concentration (cmc) and another characteristic concentration (ct) spherical micelles were detected whose radii were independent of detergent concentration and equal to the length of a detergent molecule ; the aggregation number n of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 25 publications
4
45
0
Order By: Relevance
“…This is because the effective value of c* can itself decrease with dilution due to increasing micellar size. We also note that over the past two decades, a number of other micellar solutions have also been found to exhibit the properties of dilute and semidilute solutions of linear polymers (65,(77)(78)(79)(80)(81).…”
Section: Appendix A: Analysis Of Possible Mixed Micellar Shapesmentioning
confidence: 76%
“…This is because the effective value of c* can itself decrease with dilution due to increasing micellar size. We also note that over the past two decades, a number of other micellar solutions have also been found to exhibit the properties of dilute and semidilute solutions of linear polymers (65,(77)(78)(79)(80)(81).…”
Section: Appendix A: Analysis Of Possible Mixed Micellar Shapesmentioning
confidence: 76%
“…8,[15][16][17][18][19] Some authors have added another inorganic salt, such as NaCl or KBr, to further screen the electrostatic interactions in these surfactant/salt (inorganic or organic)/water micellar systems. 16,[20][21][22] By contrast, the structural and rheological reports on salt-free viscoelastic micellar solutions are scarce. Kern et al 22 investigated the linear viscoelastic behavior of salt-free polymer-like a Departamento de Ingenier ıa Qu ımica, Universidad de Guadalajara, Boul.…”
mentioning
confidence: 99%
“…Furthermore, the size and shape of the micelles formed can be affected by the salt screening the repulsion between charged headgroups (Mazer et al 1976;Hoffmann et al 1982;Khatory et al 1993;Hassan et al 2002;Raghavan et al 2002b). Moreover, the addition of salt has an impact on catanionic aggregates, for example Brasher et al (1995) showed how an increased amount of sodium bromide caused a micelle to vesicle phase shift in a mixture of CTAB and SOS.…”
Section: Physiological Prerequisitesmentioning
confidence: 99%